Shear wave elastography measurements in dogs treated surgically for congenital extrahepatic portosystemic shunts - Toom, Merle; Saunders, Jimmy H.; Duchateau, Luc; Serrano, Goncalo; De Rooster, Hilde; Devriendt, Nausikaa; Stock, Emmelie (Frontiers in Veterinary Science, 2022)
Assessing postoperative surgical success of congenital extrahepatic portosystemic shunt (EHPSS) attenuation can be challenging and involve invasive imaging methods. Elastography is an ultrasound technique that allows qualitative and quantitative estimation of tissue stiffness and has extensively been used in people with liver disease. In recent years, increased interest for this technique has developed in veterinary medicine due to its non-invasive nature, availability, and low cost. The objective of this study was to compare liver stiffness values between dogs with closed EHPSS and those with multiple acquired portosystemic shunts (MAPSS) after gradual surgical attenuation and to assess whether shear wave elastography could be used to determine EHPSS closure. As secondary objective, measurements obtained from both intercostal and subxiphoidal views were compared. Mean values for the average, median and maximum two-dimensional shear wave velocities (2D SWV) for the closed EHPSS were 2.88 +/- 0.11 m/s; 2.83 +/- 0.11 m/s; 3.75 +/- 0.16 m/s, respectively. In the MAPSS dogs, mean values for the average, median and maximum 2D SWV were 2.77 +/- 0.17 m/s; 2.71 +/- 0.17 m/s; 3.66 +/- 0.24 m/s, respectively. No significant differences in 2D SWV were present between dogs with closed EHPSS and those with MAPSS (P=0.33; P=0.33; P=0.42, respectively). When assessing potential differences between intercostal and subxiphoidal 2D SWV measurements, no effect was observed for the average and median 2D SWV (P=0.06; P=0.07, respectively). Yet a significant difference was identified for the maximum 2D SWV between intercostal 4.00 +/- 0.20 m/s and subxiphoidal 3.41 +/- 0.17 m/s measurements (P= 0.02). The relevance of this finding is uncertain as many other studies pertaining to liver elastography only report mean and not maximum values.